PERANAN TEORI KEPUTUSAN DALAM HUKUM ADAT - Aruan, Albert; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
The study in this paper seeks to understand various views and ideas about theories regarding the decision-making process in customary law, and what traditional elders consider when making decisions. The decision-making process in customary law is very necessary in resolving the problems of disputing parties. with considerations that can be legally justified. It should be noted that in Indonesia there is no form of law or legal product outside the applicable law, so even resolving customary cases is very difficult. The applicable or written legal provisions must be a reference or guideline that must be followed by the judge handling the case. Keywords: Decision Theory, Customary Law